The Impact of Parenting on Children's Language Development - Khairunnisa Ulfadhilah; Salsabila Dwi Nurkhafifah (Child Kingdom : Jurnal Pendidikan Anak Usia Dini, 2024)
Fathers and mothers have a very important, even major role in children's growth and development, including early childhood language development, so various stimulations are needed for children to train children's language vocabulary. However, if the parenting style given to the child is not good, it results in language delays and even the child's vocabulary does not increase as the child gets older, then this is very important. Next, the author conducted research on similar things in order to add references for parents and then give children good and appropriate stimulation. The research site at RA Miftahul Huda carries out descriptive qualitative methods to explain the results of the research that has been carried out. Apart from that, to add to the research results, the author made observations with RA Miftahul Huda and then conducted interviews with school principals, teachers and parents who implemented appropriate or inappropriate parenting patterns in terms of providing stimulation for children's language development from an early age.